An Assessment of Completeness of Notifiable Disease Reporting in Jaffna District: A qualitative study - Chandrasekar, K.; Mahesan, S. (Jaffna Science Association, 2016)
Communicable diseases have been identified as one of the major health problems in developing countries. The notifiable disease surveillance system of Sri Lanka depends extensively on the inpatient-based data, collected from government hospitals of the western medical system. Further, the existing surveillance systems do not receive notifications from other relevant sources. This results in incomplete reporting of notifiable diseases. This exploratory study proposed to identify all the possible sources of notification in Jaffna, and reveal the problems of these sources in relation to notification. A qualitative approach that is suitable for this kind of exploratory study, using in-depth semi-structured interviews, was chosen to collect information about their perception of, and problems within the existing system for reporting of notifiable diseases and suggestions for improvement in performance. This study was carried out during the period 2007-2010, and 38 staff members who engaged in notifiable disease surveillance activities participated in the in-depth, semi-structured interviews, each of 25-50 minutes duration. The interviewees consisted of 20 notifiers, 12 reporting staff and six administrative staff, and all interviews were conducted with the help of an interview guide. All the 38 interviews were tape-recorded with the consent of participants, fully transcribed, and analyzed by using thematic analysis approach. Study revealed that incompleteness is one of the main causes for the poor surveillance data reporting in Jaffna. In order to improve the completeness of reporting in Jaffna, it was found that, in addition to western medical practitioners in the government sector, other sources should also be incorporated into the notification system to improve the completeness of reporting in Jaffna. The sources such as indigenous medical practitioners, western medical practitioners in the private sector, public health workers, medical laboratories, educational institutions, civil service officers and general public are the other major sources than the western medical practitioners in the government sector that have to be incorporated. This would help to get the notification in time, and would results in complete reporting of notifiable diseases.
Keywords: Communicable disease surveillance; Disease notification; Infectious diseases